Increased urinary level of oxidized nucleosides in patients with mild-to-moderate Alzheimer's disease - Lee, Sang Hee; Kim, Inseong; Chung, Bong Chul (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
Objective: Oxidative stress may play an important role in the pathogenesis of Alzheimer's disease (AD). Design and methods: To investigate the possible role of oxidative DNA damage in the pathogenesis of AD, we measured the metabolite concentrations of oxidized nucleosides (pseudouridine, 1-methyladenosine, 5-methylcytidine, 5-methyl-2 '-deoxycytidine, 3-methyluridine, N-2, N-2-dimethylguanosine, 8-hydroxy-2 '-deoxyguano sine, 5-deoxyadenosine and 2-deoxyguanosine) in urine between AD (n=36) and control subjects (n=34) using liquid chromatography-mass spectrometry (LC-MS) without urine preparation. Results: In AD, the 3-methyluridine, 1-methyladenosine, 8-hydroxy-2 '-deoxyguanosine (p < 0.05, respectively), 2-deoxyguanosine (p < 0.01) and pseudouridine, N-2, N-2-dimethylguanosine (p < 0.001, respectively) were significantly increased when compared with the control subjects. Conclusion: The results indicate that oxidized urinary nucleosides may be useful as biomarkers for AD in early stages. (c) 2007 The Canadian Society of Clinical Chemists. Published by Elsevier Inc. All rights reserved.
Keywords: OXIDATIVE DNA-DAMAGE; LIPID-PEROXIDATION; PROTEIN OXIDATION; BRAIN; STRESS